The Implementation of Class Supervision and Its Positive Impact - Lisliana, Lisliana; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2020)
This research provided the implementation of supervision and its impact on teacher’s performance in Madrasah Aliyah Negeri 1 Banyuasin. The method used was descriptive qualitative. The results obtained that class supervision was carried out well in a structured or systematic manner. Class supervision is first scheduled, then good planning is arranged in relation to the things needed to carry out supervision, then supervision is carried out in class by involving each element, until finally a report on the implementation of supervision is conducted and there are recommendations for improvement to be followed up. The implementation of classroom supervision has a positive impact on teachers. That supervision is able to provide guidance to planning, implementation and evaluation of learning.